Radiofrequency Ablation for Management of Lumbar Facet Syndrome: A Case Series - Ahmed ElSayed, MD. (Egyptian Spine Association, 2018)
Background data: Radiofrequency Ablation (RFA) procedure for Lumbar facet arthritis and pain is a promising option for management of chronic low back pain due to facet arthropathy. Purpose: The aim of this study is to evaluate the clinical outcomes in patients treated with Radiofrequency Ablation for lumbar facet syndrome. Study Design: A retrospective clinical study. Patients and Methods: Eighteen consecutive patients diagnosed with Lumbar Facet Syndrome were included in this study. The Radiofrequency Ablation procedure for Lumbar facets was performed for all of them in the period between 2016 and 2017. The clinical outcome was assessed by the Visual Analogue Scale (VAS) before procedure and at follow-up. Overall patients’ satisfaction from the procedure outcome was graded according to Odom's criteria. Results: Among the eighteen patients included in the study, eight patients were females and ten were males. The mean age was 46.5±6 (33-60)years. Duration of pain at presentation varied between 1-4 years with mean duration of 30.2 months. Fourteen (77.7%) patients received bilateral facet denervation while only four had unilateral facet ablation. After the intervention, the mean Visual Analog Score for back pain was significantly improved from 7.1±1.4 to 3.0±1.2 (P=0.01).At the end of the follow up, patient satisfaction according to Odom’s criteria of outcome grading showed 34.8% of patients had good recovery and 30.2% had fair recovery. Conclusion: Radiofrequency Ablation is an emerging treatment for lumbar facet syndrome; it improves the clinical outcome on short-term follow-up. Further studies are encouraged to assess its long term efficacy. (2018ESJ126)